OTU-004 Shallow whole-genome sequencing predicts the future cancer risk of low-grade dysplastic lesions in ulcerative colitis. (8th June 2018) - Bakir, Ibrahim Al; Curtius, Kathleen; Baker, Anne-Marie; Clarke, Theo SO; Moorghen, Morgan; Jansen, Marnix; Rodriguez-Justo, Manuel; Leedham, Simon; Hart, Ailsa; Graham, Trevor
Abstract : Background: The management of low grade dysplasia (LGD) in ulcerative colitis (UC) is uncertain due to the variable risk of progression to colorectal cancer (CRC). Chromosomal copy number alterations (CNAs) occur in colonic epithelial cells of UC patients who have developed CRC. The burden of CNAs in precursor LGD relative to high-grade dysplasia (HGD) and CRC has not been defined, and the correlation between LGD CNA burden and future HGD/CRC risk is unknown. Shallow whole-genome sequencing is a novel, cost-effective technique for high resolution CNA assessment in formalin-fixed, paraffin-embedded tissue. Methods: We identified 19 UC proctocolectomy specimens with HGD/CRC, and analysed 77 neoplastic regions (36 LGD, 34 HGD and 7 CRC). We then analysed 13 'progressor' patients with 27 LGD lesions who subsequently developed HGD/CRC a median 427 days later (IQR 213–777), and 22 'non-progressor' patients with 26 LGD lesions who remained HGD/CRC-free>5 years later. The two patient groups are matched for age, gender, disease duration and LGD location. Histological diagnosis was confirmed by two blinded pathologists. Shallow whole genome sequencing (0.1x) was performed using a standardised pipeline for epithelial cell enrichment, DNA extraction, library preparation, next generation sequencing and bioinformatic analysis. Results: A median 12% of the genome of LGDs from proctocolectomy specimens showed CNAs (IQR 4%–32%), compared to 23% in HGD/CRC (IQR 19%–42%, p=0.003). Similarly, the number of CNA events was greater in HGD/CRC compared to LGD (p<0.001). Multiple CNAs involving key driver genes were more frequent in HGD/CRC compared to LGD (adjusted p-values<0.05), including 8q gain ( MYC loss, OR 17.2), 4q loss (OR 4.59) and 18q loss ( DCC/SMAD4 loss, OR 4.15). The Kaplan-Meier plot demonstrates that patients in this cohort bearing LGD with the 25% greatest CNA burden are significantly more likely to develop future CRC/HGD than the remaining 75% of patients (HR 5.1, p=0.001). Conclusions: LGD lesions demonstrate a surprising diversity in CNA burden, with some LGD lesions bearing CNA profiles indistinguishable from HGD/CRC. Shallow whole-genome sequencing has potential translational utility, by stratifying patients with LGD lesions according to risk of progression to HGD/CRC.